A Reflective Conversation With Professor Louis Markos About Myths And The Humanities? - Shaughnessy, Michael F. (European Scientific Journal, ESJ, 2020)
Louis Markos holds a BA in English and History from Colgate University and an MA and PhD in English from the University of Michigan. He is a Professor of English and Scholar in Residence at Houston Baptist University, where he holds the Robert H. Ray Chair in Humanities and teaches courses on British Romantic and Victorian Poetry and Prose, the Greek and Roman Classics, C. S. Lewis, and J. R. R. Tolkien. He is the author of twenty books, including The Myth Made Fact: Reading Greek and Roman Mythology through Christian Eyes, Ancient Voices: An Insider’s Look at Classical Greece, On the Shoulders of Hobbits: The Road to Virtue with Tolkien and Lewis, Apologetics for the Twenty First Century, From Achilles to Christ: Why Christians Should Read the Pagan Classics, Lewis Agonistes: How C. S. Lewis can Train us to Wrestle with the Modern and Postmodern World, Atheism on Trial, and The Dreaming Stone and In the Shadow of Troy, children’s novels in which his kids become part of Greek Mythology and the Iliad and Odyssey. He has produced two lecture series on C. S. Lewis and literary theory with The Teaching Company/Great Courses, published 300 book chapters, essays, and reviews, given well over 300 public lectures in some two dozen states as well as Rome, Oxford, and British Columbia, and had his adaptations of The Iphigenia in Tauris of Euripides, The Helen of Euripides, and The Electra of Sophocles performed off-Broadway. He is committed to the concept of the Professor as Public Educator and believes that knowledge must not be walled up in the Academy but must be disseminated to all who have ears to hear. Visit his amazon author page at amazon.com/author/louismarkos In this interview he responds to questions about his latest book!